1986
DOI: 10.1111/j.1365-2141.1986.tb02969.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte doubling time in chronic lymphocytic leukaemia: analysis of its prognostic significance

Abstract: In 100 untreated patients with chronic lymphocytic leukaemia (CLL) lymphocyte doubling time (LDT) has been investigated in relationship with clinical stages, bone marrow histological patterns, treatment-free period and survival. Although partially correlated with clinical stages and bone marrow patterns, LDT has a clear prognostic significance by itself: whereas a LDT of 12 or less months identifies a population of patients with poor prognosis, a LDT higher than 12 months is indicative of good prognosis as sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
120
0
9

Year Published

1987
1987
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(132 citation statements)
references
References 17 publications
2
120
0
9
Order By: Relevance
“…The prognosis of patients with CLL has been determined by the clinical staging system of Binet and Rai and also by LDT (36,37). Unfortunately, these systems fail to identify patients in early stages whose disease will rapidly progress.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients with CLL has been determined by the clinical staging system of Binet and Rai and also by LDT (36,37). Unfortunately, these systems fail to identify patients in early stages whose disease will rapidly progress.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid lymphocyte doubling time is usually defined as the doubling of peripheral blood absolute lymphocyte count (ALC) in less than 12 months. Montserrat et al reported a median survival time of over 118 months for patients with slow lymphocyte doubling times, while patients with rapid doubling times had a median survival time of only 61 months [7], which is independent of Rai stage [8]. Bcell CLL/lymphoma 2 (BCL2) expression is associated with a shorter survival time in CLL [9].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…In addition to staging systems (Rai et al, 1975;Binet et al, 1981; International Workshop on Chronic Lymphocytic Leukemia, 1989), parameters such as lymphocyte count (Galton, 1966), karyotype ( Juliusson et al, 1990), lymphocyte doubling time (Montserrat et al, 1986) and bone marrow histology (Rozman et al, 1984) have been shown to be of prognostic significance. Morphologic variability of peripheral blood lymphocytes in CLL has been recognized and some characteristics, e.g.…”
mentioning
confidence: 99%